Effect of Mass Flow Rate on Critical Heat Flux in Vertical Tube - Abdullah, Muthana L. (Nahrain University College of Engineering Journal, 2012)
The critical heat flux (CHF) in forced convective up flow has been investigated in a uniformly heated vertical steel tube of 18 mm internal diameter and 3.66 m length, with water as the working fluid. The CHF was determined by the sudden rise in the wall temperature of the electrically heated tube. Experiments were performed at nominal pressure 50 bar over three mass flux values 0.11kg/s, 0.055kg/s and 0.027 kg/s, and heat flux with up to 400 kW maximum power. The CHF results in the present experimental ranges rise linearly as the mass flux increases.Finally, a comparison of the experimental data with available fluid correlations has been performed. The present results of CHF are found to be an acceptable agreement with those predicted by using (Bowring Correlation) and are slightly higher when compared with those predicted by Katto and Ohne Correlation